Strategi Guru Dalam Meningkatkan Perkembangan Bahasa Pada Anak Usia Dini Di TK Dharma Melati Merembu Lombok Barat - Alpiana Alpiana (Indonesian Journal of Elementary and Childhood Education, 2024)
This study aims to explore the strategies used by teachers at TK Dharma Wanita Melati Merembu Lombok Barat to enhance language development in early childhood. Using a qualitative descriptive approach, the study collected data through interviews and observations with five teachers. The findings indicate that the teachers implemented four main strategies to stimulate children's language development: storytelling, singing, flash cards, and role play. The primary contribution of this research is the identification and in-depth analysis of the methods used by teachers to support language development, as well as how these strategies can be applied in educational practice. The implications of this study suggest that the use of varied teaching methods can enhance children's language skills and support their cognitive, social, and emotional development. This research provides insights for educators to optimize language teaching methods in early childhood education settings.